1989
DOI: 10.1159/000276059
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Active-Specific Immunotherapy of Lymph Node Micrometastasis in a Guinea Pig Tumor Model

Abstract: Strain 2 guinea pigs bearing the transplanted intradermally growing line 10 tumor underwent surgical tumor excision at a time when the tumor had already metastasized to the first draining lymph node. Postoperative active-specific immunotherapy (ASI) consisted of two vaccinations with either Newcastle disease virus (NDV) modified or BCG-admixed line 10 tumor cells. 32% of the animals were cured of residual lymphatic micro-metastasis by ASI with NDV-modified tumor cells while ASI with BCG was successful in 45%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…As virus in the tumor vaccine, we used NDV strain Ulster, based on good experiences in various animal tumor models and in previous clinical studies with other forms of cancer (11,14,(23)(24)(25). Recently, interest in the use of tumor-selective replication competent viruses such as NDV, which has already been safely applied to many cancer patients in Europe and the United States, is reviving (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As virus in the tumor vaccine, we used NDV strain Ulster, based on good experiences in various animal tumor models and in previous clinical studies with other forms of cancer (11,14,(23)(24)(25). Recently, interest in the use of tumor-selective replication competent viruses such as NDV, which has already been safely applied to many cancer patients in Europe and the United States, is reviving (13).…”
Section: Discussionmentioning
confidence: 99%
“…Certain proteins are selectively overexpressed in HNSCC (10), making these tumor antigens possible targets for immune recognition and reaction. In an animal model, it was shown that postoperative vaccination with irradiated, modified tumor cells could cure about one-third of the animals even after establishment of lymph node metastases (11). Furthermore, application of recombinant vaccinia virus expressing interleukin (IL)-2 as a tumor vaccine significantly improved survival of animals bearing HNSCC-tumors (6).…”
Section: Introductionmentioning
confidence: 99%
“…The present investigation of regional low-dose IL-2 immunotherapy was performed on an inbred animal tumor model which enabled us to imitate one of the major obstacles in the treatment of head and neck cancer patients: residual micrometastasis in regional lymph nodes after curative surgery of the primary lesion [19]. Both perilymphatic and intralesional low-dose IL-2 treat ment failed to influence positively the natural course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ca. 50 % der Tiere mit Mikrometastasen wurden geheilt [9,79,84]. Klinische Untersuchungen an Patienten, die postoperativ eine Vakzine aus autologen Kolon-Karzinomzellen, inkubiert mit nicht-lytischem Newcastle Disease Virus, erhalten hatten, ergaben in 39 bis 60 % der Patienten eine positive DTH-Reaktion gegen autologe Tumorzellen allein [48].…”
Section: Tumorzell-xenogeninsation Und Virale Onkolysateunclassified